Therapeutic Communication for Healing Psychological Trauma Experienced by Victims of Sexual Violence: A Literature Review - Enggal Hadi Kurniyawan; Chicha Amilia Putri; Iftita Khoiril Waroh; Nadya Anfa Askiya Irham; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur; Alfid Tri Afandi (KHD Production, 2024)
Victims of sexual violence have psychological trauma. In handling victims of sexual violence, a holistic approach needs to be taken to overcome the trauma experienced. The holistic approach is carried out using therapeutic communication. Therapeutic communication is used to support the healing process in victims of sexual violence. This research aims to find out about therapeutic communication strategies that can be applied to heal psychological trauma in victims of sexual violence. This research was conducted using a literature review by searching through three databases (Google Scholar, PubMed, and Science Direct). The search used several keywords in English and Indonesian. The literature review research shows that there are several stages in therapeutic communication for victims of sexual violence, namely pre-interaction, introduction, work, and termination. In addition to these four stages, there are three stages in therapeutic communication used in trauma recovery: pre-counseling, counseling process, and post-counseling stages. The literature study was conducted with ten articles that discuss therapeutic communication in victims of sexual violence; there are three main discussions, namely, the first discusses the stages of therapeutic communication, the second discusses the techniques that can be applied in conducting therapeutic communication, and the last discusses the benefits obtained by applying therapeutic communication in handling victims of sexual violence. From the literature review study conducted, the application of therapeutic communication to victims of sexual violence has proven to help handle the healing of psychological trauma experienced by victims of sexual violence.